The effect of product quality and price toward repurchase intention at Taco Casa Bali during Covid-19 pandemic - Werdiastuti, Putu Ema; Agustiono, Agustiono (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Due to Covid-19 pandemic, sales and the number of visitors to Taco Casa Bali have decreased. In this changing situation, repurchase intention is very important for the continuity of the culinary business, so it is important to find out the factors that influence it. The research aimed to determine the effect of product quality and price in influencing customer satisfaction on customer repurchase intentions at Taco Casa Bali during Covid-19 pandemic. Although variables in this research are not new, there is still inconsistency in the findings and also this paper factors in Covid-19 pandemic situation. Sample size consisted of 97 respondents. Using Smart-PLS version 3.9, results showed that product quality does not affect the customer repurchase intention. Price and customer satisfaction affect the customer repurchase intention. Product quality and price affect customer satisfaction. Customer satisfaction does not act as a mediator for product quality and price on customer repurchase intention. Implications of practice for this paper are discussed in the end of section.